Diet modulates metabolic and hepatic responses to chronic pesticide mixture exposure in mice - C. Rives; N. Poirier-Jaouen; Y. Malaisé; C. M. P. Martin; M. Huillet; S. Ellero-Simatos; P. Perrier; A. Polizzi; F. Lasserre; V. Alquier-Bacquié; C. Guyon; Y. Lippi; et al. (Archives of Toxicology, 2026)

Coral restoration through the optimization of early life-stage dynamics: The case of the Mediterranean red coral (Corallium rubrum) - B. Giordano; K. Guizien; C. Ferrier-Pagès; S. Reynaud; E. Manea; E. Beraud; A. Catania; M.I. Marcus Do Noscimento; Al. Cau; G. Loentgen; R. Cannas; C. Rottier; et al. (Biological Conservation, 2026)

Positive Interactions Under Ocean Warming and Acidification: Crustose Coralline Algae Holobionts Enhance Gorgonian Larval Settlement Under Climate Change - E. Manea; P. E. Galand; S. Comeau; C. Ferrier‐Pagès; B. Giordano; L. Pezzolesi; J.‐B. Raina; S. N. Elahee Doomun; R. Tignat‐Perrier; L. Bramanti (Environmental Microbiology, 2025)
Crustose coralline algae (CCA) and their bacterial communities can emit chemical cues favoring coral larval settlement. Indeed, larvae of Eunicella singularis (white gorgonian) preferentially settle on CCA. Here, we investigated the effect of two Mediterranean CCA holobionts, Macroblastum dendrospermum and Lithophyllum stictiforme , on E. singularis larvae settlement and their bacterial communities, after warming and acidification treatments. We exposed CCA to temperature and pH expected for 2100 (SSP5‐8.5) and to a marine heatwave event. Larval settlement increased 1.8–2.7 times in the presence of CCA exposed to warming and acidification compared to non‐exposed CCA. High abundance of bacteria belonging to the Pirellulaceae family was observed in all CCA, while a higher abundance of monosaccharides was found in exudates of exposed CCA. Based on CCA‐related 16S rDNA metabarcoding and metabolomics results, we hypothesize that the enhanced larval settlement was driven by the Pirellulaceae breakdown and utilization of CCA polysaccharides, in combination with polysaccharide release through the CCA cell walls likely augmented by decalcification. Furthermore, CCA acted as sources of bacterial taxa that may establish and persist in the adult E. singularis holobiont, independently of climate change effects. We conclude that CCA are key for E. singularis recruitment success, especially under future climate conditions, and contribute to their microbiome development.

P17-06 Advances in the Delayed-Type Hypersensitivity (DTH) assessment in Non-Human Primates: The Added Value of Multiple Readouts - M. Carrière; A. Perrier; S. Bonavaud; C. L'Huillier; N. Colliou; C. Thirion-Delalande; M. Ciurkiewicz; F. Gervais; R. Gravier; P. Ancian (Toxicology Letters, 2025)

An operational discontinuous Galerkin shallow water model for coastal flood assessment - A.G. Filippini; L. Arpaia; V. Perrier; R. Pedreros; P. Bonneton; D. Lannes; F. Marche; S. De Brye; S. Delmas; S. Lecacheux; F. Boulahya; M. Ricchiuto (Ocean Modelling, 2024)

The use of long-read PCR amplicon sequencing to study the evolution of resistance to zoxamide, oxathiapiprolin and complex III inhibitors in French Plasmopara viticola field populations - S. Cherrad; B. Gillet; J. Dellinger; L. Bellaton; P. Roux; C. Hernandez; H. Steva; L. Perrier; S. Vacher; S. Hughes (Journal of Plant Diseases and Protection, 2024)

Surface temperatures of non-incubated eggs in great tits (Parus major) are strongly associated with ambient temperature - Marcel M. Lambrechts; Aude E. Caizergues; Charles Perrier; Anne Charmantier; Samuel P. Caro (International Journal of Biometeorology, 2020)

Deoxynivalenol inhibits the expression of trefoil factors (TFF) by intestinal human and porcine goblet cells - Fabien Graziani; Philippe Pinton; Hamza Olleik; Ange Pujol; Cendrine Nicoletti; Mehdi Sicre; Nathalie Quinson; El Hassan Ajandouz; Josette Perrier; Eric Di Pasquale; Isabelle P. Oswald; Marc Maresca (Archives of Toxicology, 2019)

Investigating genomic and phenotypic parallelism between piscivorous and planktivorous lake trout ( Salvelinus namaycush ) ecotypes by means of RAD seq and morphometrics analyses - S. Bernatchez; M. Laporte; C. Perrier; P. Sirois; L. Bernatchez (Molecular Ecology, 2016)
Repeated adaptive ecological diversification has commonly been reported in fish and has often been associated with trophic niche diversity. The main goal of this study was to investigate the extent of parallelism in the genomic and phenotypic divergence between piscivorous and planktivorous lake trout ecotypes from Laurentian Shield lakes, Canada. This was achieved by documenting the extent of morphological differentiation using geometric morphometrics and linear measurements as well as the pattern of genomic divergence by means of RAD seq genotyping (3925 filtered SNP s) in 12 lakes. Our results indicate that the two ecotypes evolved distinct body shape and several linear measurements in parallel. Neutral genetic differentiation was pronounced between all isolated populations (Mean F ST = 0.433), indicating no or very limited migration and pronounced genetic drift. Significant genetic differentiation also suggested partial reproductive isolation between ecotypes in the two lakes where they are found in sympatry. Combining different outlier detection methods, we identified 48 SNP s putatively under divergent selection between ecotypes, among which 10 could be annotated and related to functions such as developmental processes and ionic regulation. Finally, our results indicate that parallel morphological divergence is accompanied by both parallel and nonparallel genomic divergence, which is associated with the use of different trophic niches between ecotypes. The results are also discussed in the context of management and conservation of this highly exploited species throughout northern North America.

Genomic resources and their influence on the detection of the signal of positive selection in genome scans - S. Manel; C. Perrier; M. Pratlong; L. Abi‐Rached; J. Paganini; P. Pontarotti; D. Aurelle (Molecular Ecology, 2016)
Genome scans represent powerful approaches to investigate the action of natural selection on the genetic variation of natural populations and to better understand local adaptation. This is very useful, for example, in the field of conservation biology and evolutionary biology. Thanks to Next Generation Sequencing, genomic resources are growing exponentially, improving genome scan analyses in non‐model species. Thousands of SNP s called using Reduced Representation Sequencing are increasingly used in genome scans. Besides, genome sequences are also becoming increasingly available, allowing better processing of short‐read data, offering physical localization of variants, and improving haplotype reconstruction and data imputation. Ultimately, genome sequences are also becoming the raw material for selection inferences. Here, we discuss how the increasing availability of such genomic resources, notably genome sequences, influences the detection of signals of selection. Mainly, increasing data density and having the information of physical linkage data expand genome scans by (i) improving the overall quality of the data, (ii) helping the reconstruction of demographic history for the population studied to decrease false‐positive rates and (iii) improving the statistical power of methods to detect the signal of selection. Of particular importance, the availability of a high‐quality reference genome can improve the detection of the signal of selection by (i) allowing matching the potential candidate loci to linked coding regions under selection, (ii) rapidly moving the investigation to the gene and function and (iii) ensuring that the highly variable regions of the genomes that include functional genes are also investigated. For all those reasons, using reference genomes in genome scan analyses is highly recommended.

Parallel and nonparallel genome‐wide divergence among replicate population pairs of freshwater and anadromous A tlantic salmon - Charles Perrier; Vincent Bourret; Matthew P. Kent; Louis Bernatchez (Molecular Ecology, 2013)
Little is known about the genetic basis differentiating resident and anadromous forms found in many salmonid species. Using a medium‐density SNP array, we documented genomic diversity and divergence at 2336 genetically mapped loci among three pairs of North American anadromous and freshwater Atlantic salmon populations. Our results show that across the genome, freshwater populations have lower diversity and a smaller proportion of private polymorphism relative to anadromous populations. Moreover, differentiation was more pronounced among freshwater than among anadromous populations at multiple spatial scales, suggesting a large effect of genetic drift in these isolated freshwater populations. Using nonhierarchical and hierarchical genome scans, we identified hundreds of markers spread across the genome that are potentially under divergent selection between anadromous and freshwater populations, but few outlier loci were repeatedly found in all three freshwater–anadromous comparisons. Similarly, a sliding window analysis revealed numerous regions of high divergence that were nonparallel among the three comparisons. These last results show little evidence for the parallel evolution of alleles selected for in freshwater populations, but suggest nonparallel adaptive divergence at many loci of small effects distributed through the genome. Overall, this study emphasizes the important role of genetic drift in driving genome‐wide reduction in diversity and divergence in freshwater Atlantic salmon populations and suggests a complex multigenic basis of adaptation to resident and anadromous strategies with little parallelism.

Radon Emanation in Partially Saturated Porous Media - P. M. Adler; F. Perrier (Transport in Porous Media, 2009)

Yellow leaf of sugarcane is caused by at least three different genotypes of sugarcane yellow leaf virus, one of which predominates on the Island of Réunion - Y. Abu Ahmad; L. Rassaby; M. Royer; Z. Borg; K. S. Braithwaite; T. E. Mirkov; M. S. Irey; X. Perrier; G. R. Smith; P. Rott (Archives of Virology, 2006)

Long-term climate change and surface versus underground temperature measurements in Paris - F. Perrier; J.-L. Le Mouël; J.-P. Poirier; M. G. Shnirman (International Journal of Climatology, 2005)

Pressure-induced Shape Change of Phospholipid Vesicles: Implication of Compression and Phase Transition - J.-M. Perrier-Cornet; K. Baddóuj; P. Gervais (The Journal of Membrane Biology, 2005)

Molecular diversity in pineapple assessed by RFLP markers - M. F. Duval; J. L. Noyer; X. Perrier; Coppens d’Eeckenbrugge; P. Hamon (Theoretical and Applied Genetics, 2001)

A new aspect of genetic diversity of Indonesian oil palm (Elaeis guineensis Jacq.) revealed by isoenzyme and AFLP markers and its consequences for breeding - A. R. Purba; J. L. Noyer; L. Baudouin; X. Perrier; S. Hamon; P. J. L. Lagoda (Theoretical and Applied Genetics, 2000)

Fatty acid and carotenoid composition ofRhodotorula strains - V. Perrier; E. Dubreucq; P. Galzy (Archives of Microbiology, 1995)